Choosing to Be Trained: Do Behavioral Traits Matter? - Utteeyo Dasgupta; Lata Gangadharan; Pushkar Maitra; Subha Mani; Samyukta Subramanian (Institute for the Study of Labor (IZA), 2014)
In this paper, we examine the determinants of self-selection into a vocational training program in India. To do this we combine data from an artefactual field experiment with survey data collected from the targeted community. We find that applicants and non-applicants differ in terms of socio-economic characteristics (measured using a survey), as well as selected behavioral traits (elicited using an artefactual field experiment). Even after controlling for a range of socio-economic characteristics, we find that individuals who have higher tolerance for risk, and are more competitive, are more likely to apply to the training program. This suggests that focusing only on the socio-economic and demographic characteristics might not be sufficient to fully explain selection into the program. Participants' behavioral traits are also crucial in influencing take up rates in such programs. Our results suggest that as a methodology, there is valuable information to be gained by dissecting the black box of unobservables using data on behavioral traits.
Keywords: J24; C93; C81; 330; selection; artefactual field experiment; behavioral traits; household survey; training program